STUDI KELAYAKAN PENGELOLAAN KAWASAN PECINAN LASEM, KABUPATEN REMBANG, JAWA TENGAH, BERBASIS EKOMUSEUM - , SALSABILLA SAKINAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Topic: This research is a museology study, focusing on feasibility study of implementing ecomuseum-based management concept in Lasem Chinatown, Rembang Regency, Central Java. Research Question and Goals: Research question: Is Lasem Chinatown feasible to be managed by ecomuseum-based concept? Goals: 1. Studying the feasibility of Lasem Chinatown to be managed by ecomuseum-based concept. 2. If the result shows that Lasem Chinatown is feasible, the other goal is to give some general strategies to preparing the implementation of that concept. Method: This research uses explorative-descriptive inductive logic. Data collecting is conducted by observation, interview, and literature study. Data analysis is conducted by using SWOT Strength, Weakness, Opportunity, and Threat) approach to analyzing the feasibility of Lasem Chinatown to be managed by ecomuseum-based concept. Conclusion: The result of this study shows that Lasem Chinatown is feasible to be managed by ecomuseum-based concept. To preparing Lasem Chinatown for implementation of the ecomuseum-based management model, there are some general strategies i.e.: preparing the legal standing in regency regulation, building society awareness of heritage, and revitalizing some natural and socio-cultural environment elements.